The impact of physical and sports activities in school psychological level of alienation a among some primary school students aged 9-10 years. - Khames, Saad (Journal of Physical Education, 2015)
Find a goal to prepare the scale to measure the level of alienation psychological among primary school students aged 9-10 years in the physical education lesson.The second objective was to identify the effect of physical activity and sports school in the level of psycholo gical alienation of pupils agead 9-10 years in the devlopment of some physical and motor abilities in physical education lesson.The research hypothesis was there significant differences morally results between tribal and dimensional measurements in the level psychological alienation find the smple.The researcher used_ guasi experimental design one group which is applied to the use of the indepependent variable the commuity find fourthe grade pupils of the school of mole and culture alaatdaiah to taling (205) studeents. The research sample was chosen by lot divided abe first two smple to a prvate experience expedditionary division of school mole primary and the (22) pupils to build and (12) syudents form the division of cultrue elementary school were randomly selected for the implementation of the key experment. Psychological students of primary gauge. The researcheres used the areas of psychological elienation that you used to praise researcher joseph (hyena scale)(2004).The areas of scale (4)areas.Perpresented the basic themes in the physhologial phenomenon of alienation and axis in the(social_ alamaarah_ deficit_ alamanay.The researcher conducting the pre_ jest on wendnesday,a brief summary 12/3/2014.Find the samply througy the distrbution of psychological alienation. and dopted researcher physical activity lessons of physical Education and guestrooms (2) he studied the weeks activity ,but ad descriptive one serving per week through the establishment of sports racing games has handball ,volleyball, relayraces for a period of seven weeks and by (21) units and (14) eduational units throug physical education lesson and (7) units educational activity that is not descriptive and accurate time lesson (40) minute. Began on Thursday a brief summary 13/3/2014 until day Thursday a brief summary 27/4/2014. In order to arrive to the search rusults were statistically using data processing S.pss.One of the main conclusions reached by researcher: The physical activites and sports play on important role in reducing the level of social isolation and deficit a mong students. The researcher recommended: The adoption of physical activity and sports in reducing the level of psychological alienation bamiv primary school